The General Movements Assessment in Neonates With Hypoxic Ischemic Encephalopathy. (July 2021) - Pouppirt, Nicole R.; Martin, Valerie; Pagnotto-Hammitt, Linda; Spittle, Alicia J.; Flibotte, John; DeMauro, Sara B.
Background: Clinical measures after birth and studies such as electroencephalogram (EEG) and brain imaging do not fully predict neurodevelopmental outcomes of infants with hypoxic-ischemic encephalopathy. Early detection of adverse neurologic outcomes, and cerebral palsy in particular, in high-risk infants is essential for ensuring timely management. The General Movements Assessment is a tool that can be used in the early detection of cerebral palsy in infants with brain injury. The majority of studies on the General Movements Assessment in the late preterm and term population were performed prior to the introduction of therapeutic hypothermia. Aims: To apply the General Movements Assessment in late preterm and term infants with hypoxic-ischemic encephalopathy (including those who received therapeutic hypothermia), to determine if clinical markers of hypoxic-ischemic encephalopathy predict abnormal General Movements Assessment findings, and to evaluate interrater reliability of the General Movements Assessment in this population. Study design: Pilot prospective cohort study Subjects: We assessed 29 late preterm and full-term infants with mild, moderate, and severe hypoxic-ischemic encephalopathy in Philadelphia, PA. Results: Most infants' general movements normalized by the fidgety age. Only infants with moderate or severe hypoxic-ischemic encephalopathy had abnormal general movements in both the writhing and the fidgety ages (n = 6). Seizure at any point during the initial hospitalization was the clinical sign most predictive of abnormal general movements in the fidgety age (sensitivity 100%, specificity 55%, positive predictive value 40%, negative predictive value 100%). Interrater reliability was greatest during the fidgety age (κ = 0.67). Conclusions: Seizures were the clinical predictor most closely associated with abnormal findings on the General Movements Assessment. However, clinical markers of hypoxic-ischemic encephalopathy are not fully predictive of abnormal General Movements Assessment findings. Larger future studies are needed to evaluate the associations between the General Movements Assessment and childhood neurologic outcomes in patients with hypoxic-ischemic encephalopathy who received therapeutic hypothermia.